The effect of black tea supplementation on blood pressure: a systematic review and dose–response meta-analysis of randomized controlled trials. Issue 1 (25th November 2020) - Ma, Chang; Zheng, Xuehui; Yang, Yi; Bu, Peili
Abstract : The main goal of this work was to clarify the effects of black tea supplementation on blood pressure by performing a systematic review according to the PRISMA guidelines, followed by a dose–response meta-analysis of randomized controlled trials. Abstract : The main goal of this work was to clarify the effects of black tea supplementation on blood pressure (BP) by performing a systematic review according to the PRISMA (preferred reporting items for systematic reviews and meta-analyses) guidelines, followed by a dose–response meta-analysis of randomized controlled trials (RCTs). Electronic search was carried out in PubMed, Embase and the Cochrane Library databases published up to March 2020. To be included, RCTs had to report the effect of black tea supplementation on systolic blood pressure (SBP) or diastolic blood pressure (DBP) in adults. A total of 13 trials, including 22 study arms were eligible for inclusion in the final quantitative analysis. It was observed that black tea supplementation significantly reduced SBP (WMD – 1.04 mmHg; 95% CI – 2.05 to −0.03; and P = 0.04) and DBP (WMD – 0.59 mmHg; 95% CI – 1.05 to −0.13; and P = 0.01) compared to the control. However, nonlinear analysis failed to indicate a significant influence of black tea flavonoid supplementation dose or duration on both SBP and DBP. Sensitivity analysis showed that no individual study had a significant impact on our results. In addition, we found no evidence for the presence of small-study effects among studies for both SBP and DBP. Thus, the favorable effect of black tea supplementation emerging from the current meta-analysis suggests the possible use of this tea as an active compound in order to promote cardiovascular health, mostly when used for longer duration (>7 days) and in men. Furthermore RCTs using different doses of black tea and various durations may contribute to confirming our conclusion.